2018
DOI: 10.1111/rda.13254
|View full text |Cite
|
Sign up to set email alerts
|

miR‐26a inhibits proliferation and promotes apoptosis in porcine immature Sertoli cells by targeting the PAK2 gene

Abstract: Accumulating reports have demonstrated that microRNAs (miRNAs) participate in regulating the complex processes of animal testis development and spermatogenesis; yet, the mechanisms by which miRNAs regulate spermatogenesis are poorly understood. miR-26a was identified as a miRNA that is differentially expressed among different pig testicular tissue developmental stages in our previous study. In this study, p21 activated kinase 2 (PAK2) gene was determined as one target gene of miR-26a by luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…h The quantification of PLCβ1 protein. *P < 0.05, **P < 0.01, ***P < 0.001, PLCβ1, phospholipase C beta 1; UTR, Untranslated Region; ST, swine testis; NC, negative control; N.S., nonsignificant processes of animal testis development and spermatogenesis via their regulations of cell proliferation, apoptosis, and differentiation [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…h The quantification of PLCβ1 protein. *P < 0.05, **P < 0.01, ***P < 0.001, PLCβ1, phospholipase C beta 1; UTR, Untranslated Region; ST, swine testis; NC, negative control; N.S., nonsignificant processes of animal testis development and spermatogenesis via their regulations of cell proliferation, apoptosis, and differentiation [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs may serve potential roles in regulating testis development, and their speci c expressions may induce the differences in sexual maturity and spermatogenesis. A growing number of reports have revealed that miRNAs play important roles in the complex processes of animal testis development and spermatogenesis via their regulations of cell proliferation, apoptosis, and differentiation [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm motility, kinetics, vigor and hyperactivation levels, are morphofunctional features classically assessed by light microscopy or computer-assisted sperm analysis (i.e., CASA) (Vincent et al, 2012). In addition, since sperm motility requires a substantial amount of energy produced by mitochondrial activity (Piomboni et al, 2012), high fertility samples usually present with high mitochondrial membrane potential. This feature can be assessed by fluorescence microscopy and flow cytometric approaches mainly using the JC-1 fluorescent probe, which forms J-aggregates when mitochondria are active FIGURE 1 | Concept of "healthy (viable) sperm."…”
Section: Morpho-functional Sperm Featuresmentioning
confidence: 99%